Penguatan Karakter dan Pelestarian Budaya Lokal Melalui Permainan Tradisional - Rien Anitra; Mertika; Evinna Cinda Hendriana; Emi Sulistri; Wasis Suprapto; Dina Anika Marhayani (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2026)
In this digital era, children are increasingly playing online games, making it important to remember the richness of traditional games. Traditional games are an effective means of preserving local culture, not only for fun but also for building character, such as patience and critical thinking skills. This community service activity, using lectures, questions and answers, demonstrations, simulations, and practical exercises, aims to educate and understand the importance of character and preserving local culture among students at Singkawang 89 Public Elementary School. The response results showed that 100% of students considered the community service activity on traditional games very beneficial, proving that this approach was right on target. This program successfully reintroduced cultural heritage to the younger generation while providing real educational benefits, especially in character building. Students were able to understand and realize that traditional games provide many benefits and are no less enjoyable than playing games on gadgets.).